« The show must go on » ou comment ralentir la chute - Laure Depretto (TV Series, 2015)
This article analyses the three behind-the-scenes shows created by Aaron Sorkin, Sports Night, Studio 60 on the Sunset Strip and The Newsroom, especially their ability to last. By adopting a descriptive angle (how does a TV show work? what are its economic constraints?), they have adopted a short-range tension instead of a long-term suspense (will the characters complete their show in time?). First we will study the three pilots which are launching an identical story arc (i.e., the tension between quality and profit), then the narrative techniques the three series use to slow down or accelerate the ending. By doing so, we will examine the serial and cyclic nature of these series as well as the various strategies enabling them to last or start anew, including the insertion of sideways suspense stories.